Probable Enalapril Hepatotoxicity in a 13-Year-Old Male Western Lowland Gorilla: Pharmacologic Risks and Vigilance - Gamble, Kathryn C.; Lovstad, Jessica N.; Gustavsen, Kate A. (Frontiers in Veterinary Science, 2019)
A 13-year-old male Western lowland gorilla presented acutely with a precipitous decline in health status from liver disease. Through diagnostic assessment, including serum chemistries and advanced imaging, it was diagnosed with probable hepatotoxicity resulting from its prescribed medication, enalapril. As one of several angiotensin converting enzyme inhibitors (ACE-I) available to zoo veterinarians, enalapril had been administered for treatment of mild ventricular hypertrophy diagnosed during routine examination 2.5 years prior to the presentation. The gorilla made a complete recovery with discontinuation of this medication, and provision of hepatoprotectants. Hepatotoxicity has been documented in humans receiving this product as an adverse drug reaction and is considered both rare and unpredictable in occurrence. In this event, an association was suspected with indulgent consumption of browse offered immediately prior to clinical presentation. Although ACE-I are important medications in this taxon due to its predisposition to cardiac disease, this event underscores the need for vigilance on the part of veterinarians and managers whenever pharmaceuticals are administered. Most drugs are modeled in a limited number of species but utilized in a wide variety, and unintended results are possible.